Over and under the canyon - Messner, Kate (Messner, Kate. Over and under., 2021)
"Over the canyon, the sun scalds the air, and bakes the desert mud to stone. But under the shade of the canyon hides another world, where bighorn sheep bound from rock to rock on the hillside, roadrunners make their nests in sturdy cacti, and banded geckos tuck themselves into the shelter of the sand. This book takes readers on a journey through the wonders concealed in the curves of the canyon, and all the secret life hidden in its arms"--